Tehran city’s typing in terms of social indicators of housing - Sedaghati, Atefeh; Omrani, Sogand (International Journal of Sustainable Construction Engineering and Technology, 2017)
Housing is something more than just a physical shelter and contains all the public services facilities for the human life. Therefore, housing location environment in one hand and characteristics of resisting human on the other hand, affects the developing and formation of housing. Affective items on proposal of housing as a several dimension good vary and are so different. The heading study approaches to find majority type of housing in Tehran by scrutinizing affective items on proposal of housing in this city in terms of affective population indexes on the way of housing between 2010-2011, and this way it would be able to shed light on proposal of housing in Tehran. Researching method is kind of Analytical overview and applied survey studying. For analyzing the data the mixture of basics of numerical taxonomy methods and fuzzy logic (kind of several variable ranking method) in the environment of Arc GIS software is used. Also correlation analysis in SPSS software environment is used to acknowledge the relationship between variables and determine weights of items. All in all 6 main indexes are studied. Results show the possibility of house typing in Tehran, as accurate as statistical areas in 2011. Also the correlation between population density variables and the household, number of rooms in each residential unit on 99% of confidence level is approved. So with the knowledge of the way population indexes affect the choice of housing location, operational approaches to provide optimal pattern of settlement in Tehran could be presented.